1994
DOI: 10.1295/polymj.26.357
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Thermal Behavior of Fluorine-Containing Phenylmaleimides

Abstract: ABSTRACT:Fluorine content dependency on the melting point and thermal polymerization reactivity of fluorine-containing phenylmaleimides were investigated by differential scanning calorimetry and are discussed on the basis of molecular structure calculations. The syntheses of fluorine-containing maleimides were carried out by thermal dehydration. Their yields tended to be lower with increasing fluorine content. This was due to lowered nucleophilic reactivity of the amino group. The fluorine-containing maleimide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…14 Several studies demonstrated the incorporation of uorine containing building blocks into bismaleimide materials can effectively reduce their dielectric constants (D k ) and moisture adsorption and modify their surface properties. 29,30 However, only limited uorinated bismaleimides were prepared due to the availability and cost of the uorinated building blocks for the synthesis of bismaleimides. 31,32 It encourages us to look for new uorinated building blocks and novel synthetic methods to effectively synthesize uorinated bismaleimides with the prospects of commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…14 Several studies demonstrated the incorporation of uorine containing building blocks into bismaleimide materials can effectively reduce their dielectric constants (D k ) and moisture adsorption and modify their surface properties. 29,30 However, only limited uorinated bismaleimides were prepared due to the availability and cost of the uorinated building blocks for the synthesis of bismaleimides. 31,32 It encourages us to look for new uorinated building blocks and novel synthetic methods to effectively synthesize uorinated bismaleimides with the prospects of commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…For example, bismaleimide resin provides a thermoset product that has been applied in a wide range of composite materials. [13][14][15][16][17] The unsaturated double bond of maleimide rings can thermally polymerize [18][19][20][21][22] without the formation of volatile by-products. In several reports, 19, [23][24][25][26][27] the efficient photoinitiated polymerization by excited state of maleimides and bismaleimides have been shown in numerous (acceptor; donor) pair combinations.…”
Section: Introductionmentioning
confidence: 99%